Content Determination and Chemical Clustering Analysis of Tanshinone and Salvianolic Acid in Salvia spp. - Feiyan Wang; Yufeng Bao; Furui Yang; Lu Yuan; Xinchun Han; Yanbo Huang; Yukun Wei; Lei Zhang; Zongqi Yang; Dongfeng Yang (Metabolites, 2024)
Salvia miltiorrhiza is one of the famous traditional Chinese medicines for treating cardiovascular and cerebrovascular diseases. Tanshinone and phenolic acids are the main active compounds of Salvia miltiorrhiza, whereas the distribution patterns of the two kinds of components are still unclear among Salvia spp. In this work, high-performance liquid chromatography was applied to analyze the distribution patterns of major components in the roots and leaves of 58 Salvia spp. The results showed that the distribution patterns of tanshinone and phenolic acids in Salvia spp. varied significantly. Phenolic acid components such as rosmarinus acid, caffeic acid, and danshensu are widely distributed in the roots and leaves, and phenolic acids in the leaves of Salvia spp. are generally higher than that in roots. Tanshinones are mainly detected in the roots of Salvia przewalskii, Salvia trijuga, Salvia castanea, and Salvia yunnanensis. The content of major components of the different species varied significantly. The content of phenolic acids in most Salvia spp. generally followed the pattern of salvianolic acid B > rosmarinic acid > danshensu > caffeic acid both in the roots and leaves. Tanshinone IIA and cryptotanshinone were the main lipophilic components of Salvia spp. distributed in southwest China. A correlation between the distribution pattern of tanshinone and the genetic relationship of species was indicated in the work. This research systematically reveals the distribution patterns of tanshinone and phenolic acids in Salvia spp., providing a theoretical basis for the development and utilization of medicinal resources of Salvia.